Tantangan Penerapan Kebijakan Standart Pendidikan dan Tenaga Kependidikan di MTS Aisyiyah Tembung - Ramadayani, Sintya; Mayshara, Viani Alya; Maudina, Nazwa; S, Simamora; R, Radianti; Darmansyah, Tengku (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the challenges faced by MTs Aisyiyah Tembung in implementing the Education and Educational Personnel Standards in accordance with national regulations. The research focuses on fulfilling teacher qualifications and competencies, the implementation of continuous professional development, the availability of adequate educational personnel, as well as the application of process and assessment standards. Using a qualitative approach through observation, interviews, and document analysis, the findings reveal several major obstacles, including limited human resources that meet standard qualifications, insufficient professional training, school management that is not yet fully performance-based, and restricted funding to support the improvement of educational and administrative staff quality. Additionally, difficulties arise in curriculum adjustment and the effective execution of academic supervision. This study recommends strengthening teacher development systems, establishing cooperation with professional training institutions, optimizing school-based management, and increasing financial support from both the foundation and the government. These efforts are expected to enhance the effective and sustainable implementation of education and educational personnel standards at MTs Aisyiyah Tembung.